ANÁLISE DA EFICIÊNCIA DO CICLO DE EXECUÇÃO DE ESTRUTURA DE CONCRETO ARMADO COM USO DE MESAS VOADORAS - Cescon, Vanessa Telh; Pagnussat, Daniel Tregnago (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aim of this research is to analyse the execution of concrete structures of a 25 floors residential buildings, analysing the schedule that was not developing in the expected time, generating delays for programmed activities. The focus of the study was to identify the main factors that influence the process of the building cycle, and when possible propose improvements. The method adopted for this study includes a theoretical basis that contemplates the technological procedure adopted in the work, such as the use of flying deck formwork and prestressed slabs. In addition, methods of planning and production control were analysed, allowing a greater understanding of the organization of all the activities involved in the executive process. Results showed that the flying of deck formwork, the assembly of reinforcements and the pillars forms had taken average twice the expected time.